Toxicity of puffer fish: two species (Lagocephalus laevigatus, linaeus 1766 and Sphoeroides spengleri, Bloch 1785) from the Southeastern Brazilian coast - Oliveira,J. S. (2003)
In Brazil, where puffer fish are considered poisonous, there are few documented cases on human consumption and consequent poisoning. In this study, toxicity of two puffer fish species from the Brazilian coast was examined. Specimens of Sphoeroides spengleri and Lagocephalus laevigatus were caught in São Sebastião Channel (North coast of São Paulo State, Brazil) between January 1996 and May 1997. Acidic ethanol extracts from muscle and skin plus viscera were tested for mice acute toxicity using the standard method of Kawabata. Polar extracts of S. spengleri showed high toxicity up to 946 MU/g. Extracts from L. laevigatus showed very low levels of toxicity, never exceeding 1.7 MU/g. All extracts from both species blocked amielinic nerve fiber evoked impulses of crustacean legs; this effect reverted on washing similar to the standard tetrodotoxin TTX. The aqueous extract solutions were partially purified using an ionic exchange column (Amberlit GC-50) followed by treatment with activated charcoal (Norit-A). The presence of TTX and their analogs in the semi-purified extracts were confirmed by HPLC and mass spectrometry (MALDI-TOF).